The Usefulness of Jonas Theory in solving particular ecological problems? - Chudzik, Joanna (Studia Ecologiae et Bioethicae, 2007)
The following article attempts to answer the question if it is possible to find criteria enabling to solve the ethical-political dilemmas such as the one of Rospudy Valley on the grounds of Jonas ethical theory, the answer to this question is reconsidered in the context of Jonas philosophical project which is the establishment of ethics for life in the ontology of organic being. On the grounds of metaphysics, Jonas justifies the constitutive link between consciousness with being and the absolute good in affirmation of the importance of existence over non-existence. Jonas shows both the continuity and special discontinuity of the human being within the domain of the livings However, he is not able to support his argument that the human being is the primary object of responsibility being ahead of other forms of organic life. Jonas ethical theory ought to include the specification of moral principles that will be useful for clarifying the matters that must be preserved and defended.